Work-Life Balance and Job Burnout of Female Staff in Private Commercial Banks in Kathmandu - K.C., Sudarshan (Mangal Research Journal, 2023)
The increasing presence of women in the modern workforce poses several challenges to businesses, employees and their families. Female employees of banks play the most critical role in the delivery of quality services to customers. However, they are in stress due to the workload and diversity of customers. Female employees experience various obstacles in their professional life as well as personal life. It is a huge challenge for them to satisfy the individual needs and expectations of the organization. The aim of this paper is to investigate the impact of work-life balance on job burnout among female employees in private commercial banks in Kathmandu. It is based on a quantitative research approach with the structured questionnaire for the survey. SPSS version 25 was used to analyze the data collected from 399 respondents among 8543 female employees. The result of the study shows that surveyed female bank employees have high work-life balance with low job burnout problem. It further reveals that work-life balance has a negative impact on job burnout